Durability of Building Materials and Components - de Freitas, Vasco Peixoto de.; Delgado, J.M.P.Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Durability of Building Materials and Components provides a collection of recent research works to contribute to the systematization and dissemination of knowledge related to the long-term performance and durability of construction and, simultaneously, to show the most recent advances in this domain. It includes a set of new developments in the field of durability, service life prediction methodologies, the durability approach for historical and old buildings, asset and maintenance management and on the durability of materials, systems and components. The book is divided in several chapters that intend to be a resume of the current state of knowledge for benefit of professional colleagues.
A probabilistic approach to performance-based durability engineering -- Behavior to salt crystallization of repointing by ready-mix mortars: experimental data and application of a probabilistic model -- Influence of type of air lime and curing conditions on lime and lime-metakaolin mortars -- Performance and durability of external post-insulation: A case study -- Effects of ageing and moisture on thermal performances of ETICS cladding -- Environmental factors affecting corrosion of steel inserts in ancient masonry -- Planned preventive maintenance activities: analysis of guidance documents -- Corrosion of reinforcement in existing concrete facades -- Durability of concrete blended with micronized sands -- Chloride aging factor of concrete measured by means of resistivity, by Carmen Andrade -- The effect of concrete composition on the possibilities of accelerated testing: Carbonation.
Keywords: Building materials; Structural materials; Mechanics; Mechanics, Applied; Building Materials; Structural Materials; Solid Mechanics